Cрочно, только выделенные

0 голосов
37 просмотров

Cрочно, только выделенные


image

Алгебра (32 баллов) | 37 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

2.
\lim_{x \to \infty} ( \frac{2}{x^2}+ \frac{3}{x}-1)* \frac{7x^2-4}{2x^2+3}= \\ \\ 
= \lim_{x \to \infty} ( \frac{2}{x^2}+ \frac{3}{x}-1 )* \lim_{x \to \infty} \frac{7x^2-4}{2x^2+3}= \\ \\ 
=-1* \lim_{x \to \infty} \frac{ \frac{7x^2}{x^2}- \frac{4}{x^2} }{ \frac{2x^2}{x^2}+ \frac{3}{x^2} }=-1* \lim_{x \to \infty} \frac{7- \frac{4}{x^2} }{2+ \frac{3}{x^2} }= \\ \\ 
=-1* \frac{7}{2}=-3.5

5.
a)
g=( \frac{2}{x}-1 )cosx \\ \\ 
g'=( \frac{2}{x}-1 )'cosx+( \frac{2}{x}-1 )(cosx)'= \\ \\ 
=( -\frac{2}{x^2} )cosx-( \frac{2}{x}-1 )sinx= \\ \\ 
=- \frac{2cosx}{x^2}- \frac{2sinx}{x}+sinx= \frac{x^2sinx-2cosx-2xsinx}{x^2}

6.
y= \frac{( \sqrt{x} -3)sinx}{x^2}=x^{-2}( \sqrt{x} -3)sinx= \\ \\ 
=(x^{-2} \sqrt{x} -3x^{-2})sinx=(x^{-2+0.5}-3x^{-2})sinx= \\ \\ 
=(x^{-1.5}-3x^{-2})sinx

y'=(x^{-1.5}-3x^{-2})'sinx+(x^{-1.5}-3x^{-2})(sinx)'= \\ \\ 
=(-1.5x^{-2.5}+6x^{-3})sinx-(x^{-1.5}-3x^{-2})cosx= \\ \\ 
=(- \frac{3}{2x^2 \sqrt{x} }+ \frac{6}{x^3} )sinx-( \frac{1}{x \sqrt{x} }- \frac{3}{x^2} )cosx= \\ \\ 
=( \frac{6}{x^3}- \frac{3 \sqrt{x} }{2x^3} )sinx-( \frac{ \sqrt{x} -3}{x^2} )cosx= \\ \\ 
=( \frac{12-3 \sqrt{x} }{2x^3} )sinx-( \frac{ \sqrt{x} -3}{x^2} )cosx

(233k баллов)
0

Спасибо большое)